Behavioural Activation Therapy for Depression after Stroke (BEADS): a study protocol for a feasibility randomised controlled pilot trial of a psychological intervention for post-stroke depression - Thomas, Shirley A.; Coates, Elizabeth; das Nair, Roshan; Lincoln, Nadina; Cooper, Cindy; Palmer, Rebecca; Walters, Stephen J.; Latimer, Nicholas R.; England, Timothy J.; Mandefield, Laura; Carter, Tim; Callaghan, Patrick; et al. (BioMed Central, 2016)
Background